Income Smoothing: The Role of Management: A Comment. - Imhoff, Eugene A. (The Accounting Review, 1975)
Abstract Comments on the research efforts concerning income smoothing practices, as reported by Carl R. Beidleman. Assumptions considered in the defense of income smoothing; Market model referred to in the defense of income smoothing; Discretionary items examined in the study.